Sosialisasi Sistem Point of Sale Berbasis Web pada Toko Rita Kosmetik - Elvina Winarto; Romindo Romindo; Yudhistira Adhitya Pratama; Okky Putra Barus (Yayasan Literasi Sains Indonesia, 2023)
Nowadays, cosmetics have become a daily necessity for women, men, and children. The cosmetics in question are not just make-up cosmetics such as powder or blush. Products such as shampoo and soap are also included as cosmetics that fall into the skincare category. Various phenomena or trends that enter Indonesia affect cosmetic sales. Rita Kosmetik Store has been running since 2004 and until now Rita Kosmetik Store is still running its business manually, using paper media. The manual process has many weaknesses, including human error, long data management, weak supervision, and low data integrity. The author then designed a web-based point-of-sale system using Laravel with a MySQL database based on these problems. The resulting point-of-sale system helps Rita Kosmetik Store owners and employees in recording, collecting, and managing business transactions, inventory is properly tracked, and the resulting reports do not take much time and are more accurate.